Development of a pharmacovigilance system in a resource-limited country: the experience of the Democratic Republic of Congo. (July 2019) - Nzolo, Didier; Kuemmerle, Andrea; Lula, Yves; Ntamabyaliro, Nsengi; Engo, Aline; Mvete, Bibiche; Liwono, Jerry; Lusakibanza, Mariano; Mesia, Gauthier; Burri, Christian; Mampunza, Samuel; Tona, Gaston
Implementation of pharmacovigilance (PV) systems in resource-limited countries is a real endeavor. Despite country- and continent-specific challenges, the Democratic Republic of the Congo (DRC) has been able to develop one of the most active PV systems in the sub-Saharan Africa. The World Health Organization (WHO) regional Office identified the DRC experience to set up a PV system for antimalarial drugs safety monitoring as a 'best practice' that needed to be documented in order to help DRC improve its PV system and to be scaled up in other African countries. In response to the WHO request, a best practices and bottlenecks analysis was conducted in 2015. This analysis was updated in 2018 in the light of the minimum requirements of the WHO to set up a PV system taking into account other guidance for PV systems. The following themes were retained for analysis: (1) creation of the national PV center; (2) implementation of PV in the health system; (3) data collection and analysis; (4) collaboration with public health programs; (5) collaboration with the National Regulatory Authority. Lessons learnt from the DRC experience show that it is possible to implement PV systems in order to promote patients' safety in resource limited sub-Saharan African countries with no guaranteed funding. The ability of national PV centers to collaborate with Public health stakeholders, including public health authorities at all levels as well as public health programs, and to use existing health information systems are considered the main key to success and may substantially reduce the cost of PV activities.